Досвід та перспективи підготовки фізичних терапевтів на кафедрі акушерства і гінекології Запорізького державного медико-фармацевтичного університету - Павлюченко, Михайло Іванович; Круть, Юрій Якович; Сюсюка, Володимир Григорович; Сергієнко, Марина Юріївна; Онопченко, Світлана Павлівна; Дейніченко, Олена Валеріївна; Кириченко, Михайло Михайлович; Pavliuchenko, M. I.; Krut, Yu. Ya.; Siusiuka, V. H.; Serhiyenko, M. Yu.; Onopchenko, S. P.; et al. (My University, 2023)
Мета статті – аналіз результатів запровадження комплексного/багаторівневого підходу до підготовки студентів, що набувають другий (магістерський) рівень вищої освіти за спеціальністю «Фізична терапія, ерготерапія» на кафедрі акушерства і гінекології Запорізького державного медико-фармацевтичного університету. The purpose of the article. Analysis of the results of the introduction of a complex/multilevel approach to the training of students acquiring the second (master's) level of higher education in the specialty "Physical therapy, occupational therapy" at the Department of Obstetrics and Gynecology of the Zaporizhia State Medical and Pharmaceutical University.
Experience and prospects of training physical therapists at the department of obstetrics and gynecology of the zaporizhia state medical and pharmaceutical university
Павлюченко М. І. - https://orcid.org/0000-0002-9235-0205; Круть Ю. Я. - https://orcid.org/0000-0002-0501-6752; Сюсюка В. Г. - https://orcid.org/0000-0002-3183-4556; Сергієнко М. Ю. - https://orcid.org/0000-0001-6795-769X; Онопченко С. П. - https://orcid.org/0000-0002-9494-0866; Дейніченко О. В. - https://orcid.org/0000-0002-8932-230X; Кириченко М. М. - https://orcid.org/0000-0002-8658-9148.
Keywords: Запорізький державний медико-фармацевтичний університет; кафедра акушерства і гінекології; другий (магістерський) рівень вищої освіти; фізична терапія; Навчально-науково-лікувальний тренінговий центр; Zaporizhia State Medical and Pharmaceutical University; Department of Obstetrics and Gynecology; second (master's) level of higher education; physical therapy; Educational, scientific and therapeutic training center